2016
DOI: 10.1530/eje-15-0791
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating osteopontin levels in adult patients with type 1 diabetes mellitus and association with dysmetabolic profile

Abstract: Objective: Osteopontin (OPN) is a sialoprotein implicated in different immunity and metabolic pathways. Capable of activating dendritic cells and inducing Th1-Th17-mediated tissue damage, OPN plays a significant role in the development/progression of several autoimmune diseases; interestingly, it was also shown that OPN participates in the acute pancreatic islets response to experimentally induced diabetes in non-obese diabetic (NOD) mice. Furthermore, OPN promotes adipose tissue dysfunction, systemic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
6
15
0
1
Order By: Relevance
“…This finding is in agreement with a previous study conducted in adult T1DM patients (14). Also, Gordin et al (22), in a 10-year follow-up study on a cohort of adult patients with T1DM, demonstrated that serum OPN level was an independent predictor of DN, of cardiovascular events, and of all-cause mortality.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This finding is in agreement with a previous study conducted in adult T1DM patients (14). Also, Gordin et al (22), in a 10-year follow-up study on a cohort of adult patients with T1DM, demonstrated that serum OPN level was an independent predictor of DN, of cardiovascular events, and of all-cause mortality.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with the findings of Karamizadeh et al (13) who found increased serum OPN levels in pediatric patients with T1DM compared with healthy children in an Iranian study. Also, our findings are in accordance with previous studies on adult T1DM patients (14). Aspord et al (15) studied the pattern of expression of 524 immune-related genes in the Langerhans cells of diabetic mice and found OPN as one of the early genes that was expressed in the primary phases of diabetes and concluded that OPN may play a vital role in T1DM.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, several studies have been performed to assess the association of OPN and predisposition to T1D. This protein has been found to be elevated in pediatric and adult patients with T1D [104][105][106]. Moreover, OPN has correlated with some clinical and biochemical parameters in T1D patients, including higher body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), lower high-density lipoprotein (HDL), and microalbuminuria [104,107].…”
Section: Type 1 Diabetesmentioning
confidence: 99%